Botanical Defenders: Evaluating the Antibacterial Potential of Allium cepa, Allium sativum, and Solanum trilobatum against Bacterial Flacherie in Bombyx mori L. - G. S. Anantha Selvi; Shenbagamoorthy Sundarraj (Microbiology and Biotechnology Research: An Overview Vol. 3, 2025)
Bacterial resistance continues to pose a significant global threat, largely driven by the excessive and inappropriate use of conventional antibiotics. This crisis necessitates the development of alternative, eco-friendly antimicrobial agents, particularly those derived from medicinal plants. Botanicals offer several advantages over synthetic drugs, including lower toxicity, reduced side effects, and cost-effectiveness. The present study evaluates the antimicrobial efficacy of three potent medicinal plants—Allium cepa (onion), Allium sativum (garlic), and Solanum trilobatum—against bacterial flacherie in the mulberry silkworm (Bombyx mori L.), a disease primarily caused by Bacillus thuringiensis and other pathogenic bacteria. Aqueous extracts of these plants were examined both in vitro and in vivo to assess their antibacterial properties. The results demonstrated significant inhibitory activity against both Gram-positive and Gram-negative bacterial strains associated with silkworm infections. These findings underline the potential of plant-based formulations as effective, sustainable alternatives for managing bacterial diseases in sericulture. Incorporating phytotherapeutic agents into silkworm health management could reduce dependency on chemical antibiotics and promote environmentally responsible practices.